2018
DOI: 10.1080/15412555.2018.1432034
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Inhibitors and Angiotensin Receptor Blockers: A Promising Medication for Chronic Obstructive Pulmonary Disease?

Abstract: Chronic obstructive pulmonary disease (COPD) is a complex disorder that primarily affects the lungs and is characterized not only by local pulmonary, but also by systemic inflammation which promotes the development of extrapulmonary and cardiovascular co-morbidities. Angiotensin converting enzyme (ACE) inhibitors and ARBs (angiotensin receptor blockers) are widely used drugs in the treatment of cardiovascular diseases, with growing evidence suggesting potential benefits in COPD patients. The purpose of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 97 publications
2
13
0
Order By: Relevance
“…COPD consists of not only a persistent lung inflammation that leads to reduced airflow but also systemic inflammation that leads to comorbidities including cardiovascular disease. Studies have implicated the renin angiotensin system (RAS) in the development of pulmonary and extrapulmonary disorders in COPD thus highlighting the potential therapeutic benefit of RAS blockade in subjects with COPD 32 . Therefore, we examined whether the angiotensin-II AT1 receptor antagonist losartan would significantly reduce lung inflammation in mice chronically exposed to CS and thus be a promising medication for the treatment of COPD and comorbid cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…COPD consists of not only a persistent lung inflammation that leads to reduced airflow but also systemic inflammation that leads to comorbidities including cardiovascular disease. Studies have implicated the renin angiotensin system (RAS) in the development of pulmonary and extrapulmonary disorders in COPD thus highlighting the potential therapeutic benefit of RAS blockade in subjects with COPD 32 . Therefore, we examined whether the angiotensin-II AT1 receptor antagonist losartan would significantly reduce lung inflammation in mice chronically exposed to CS and thus be a promising medication for the treatment of COPD and comorbid cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that ARBs ameliorate pneumonia in COVID-19 patients [ [176] , [177] , [178] , [179] ], after viral infections [ 6 , [180] , [181] , [182] , [183] , [184] , [185] , [186] ], in diabetic patients [ 187 ] and in chronic obstructive pulmonary disease [ [188] , [189] , [190] ]. Improved clinical outcome after ARB treatment of COVID-19 patients is associated with reduced IL-6 in peripheral blood, increased CD3 and CD8 T cell counts and reduced peak viral load [178 ] and lower concentrations of high-sensitivity C-reactive protein (hs-CRP) and procalcitonin (PCT) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to examine the association between β-blocker use and risk of COPD compared specifically with other antihypertensive drugs. This is important because other cardiovascular drugs (ACE inhibitors and angiotensin II receptor antagonists) also seem to have beneficial effects in COPD [27], [28].…”
Section: Discussionmentioning
confidence: 99%